Reading practices in the network of trainee teachers in Primary Education (Texto Livre, 2023)
The increased presence of adolescents and young people on the Internet has led to an interest in analysing their reading and multimodal practices, which sometimes involve the creation of spaces for reading socialisation in this context and the development of vernacular practices on the Internet (CASSANY, 2012). In this paper, we want to explore this question in greater depth, considering their reading practices on the web and the knowledge that teacher trainees in Primary Education at the University of Extremadura have about the new genres developed in this media context. For this purpose, an ad hoc questionnaire was designed in which the students reported on their reading habits and practices. The results show a scarce knowledge of the genres mentioned and very little consolidated reading habits, which makes it necessary to carry out specific work to reinforce this habit and their knowledge of the different practices.